(untitled) - Stephen Healy (Rome, 1997)
The manual is valuable to agricultural policy analysts in developing countries, as well as trade and macroeconomic policy makers who need to assess th economic and administrative implications of the Agreement on Agriculture.
Keywords: agriculture and state,economics,training manuals